Inequalities for probabilities of large deviation for sums of random variables in the case limiting stable distribution - Vaitkus, P. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Вайткус. Неравенства для вероятностей больших уклонений сумм независимых случайных величин в случае предельного устойчивого закона P. Vaitkus. Nepriklausomųjų atsitiktinių dydžių sumų didžiųjų nukrypimų tikimybių nelygybės stabiliojo ribinio dėsnio atveju